Integrasi Kawasan Industri Millennium Kecamatan Tigaraksa Kabupaten Tangerang dengan Wilayah Sekitar Menuju Kota Industri - Kokoh Widyastoro; Paramita Rahayu; Erma Fitria Rini (Desa-Kota: Jurnal Perencanaan Wilayah, Kota, dan Permukiman, 2020)
The Government of Tangerang Regency has a plan to develop an industrial city in Tangerang Regency. An industrial city is an integrated city that combines industrial estates, residential areas, and commercial areas with a high concentration of population activities. The development of industrial city has several elements that need to be integrated including the separation of industrial land use, land-use connectivity, accessibility,  infrastructure and settlements in the surrounding industrial estate. The Millennium industrial estate is the largest industrial estate which develops in central area of Tangerang Regency. The purpose of this study is to what extent the Millennium industrial Estate is integrated with surrounding areas towards fulfilling the concept of industrial city. This research uses quantitative methods using descriptive analysis with Guttman Scale. The analyzes are performed on each sub-variable supported by space syntax analysis, GIS and VCR analysis to confirm the value into Guttman Scale. The results of the analysis showed that the Millennium industrial estate has been integrated in terms of land use planning, accessibility, availability of public green space, and industrial infrastructures. While the elements of availability of industrial separation zones, connectivity and location of settlements are still not integrated Based on the theory, issues and analysis, the results obtained that the integration of the Millennium industrial Estate with the surrounding areas has fulfilled 50% of requirements to develop an integrated industrial city.